Preterm Delivery: Role of Zinc - Sultana, Masuda; Jahan, Nasim; Sultana, Nayma; Quraishi, Shamshad Begum; Chowdhury, Tasrina Rabeya (Journal of Bangladesh Society of Physiologist, 2010)
Background: Preterm delivery is a very challenging obstetric complication in Bangladesh. Reduced serum zinc (Zn) concentration of the pregnant mother may have some role in causing preterm delivery. Objectives: To measure serum zinc level in preterm delivery mother and their respective neonates to observe their status. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Mitford Hospital, Dhaka, during the period of 1st January to 31st December 2009. A total 136 subjects were included in this study, of whom 27 were full term delivery mother with their respective neonates (group B), treated as control group and another 27 were preterm delivery mothers with their respective neonates (group C), treated as study group. Age ranged of preterm and full term mother were from 20-40 years. Again, 28 non pregnant women with age range from 20-30 years were taken as reference value (groupa A). Statistical analysis was done by using appropriate method as applicable. Results: Mean serum zinc level was significantly (p<0.001) lower in preterm mother in comparison to that of full term mother and also in preterm neonates than that of full term neonates. Serum total protein and albumin were significantly (p<0.001) lower in preterm mother than those of full term mother and also in preterm neonates than those of their respective mothers and full term neonates. Again, maternal serum zinc level showed positive correlation with birth weight of neonates and also with zinc concentration of neonatal blood. Conclusions: The present study revealed a lower level of serum zinc in pre-term delivery mother and their neonates. These hypozincemia may be responsible for low birth weight of the fetus. Key Words: Zinc; preterm DOI: 10.3329/jbsp.v5i1.5415 J Bangladesh Soc Physiol. 2010 June; 5(1): 27-33